ACCURACY OF PEDICLE SCREW INSERTION: A COMPARISON BETWEEN FLUOROSCOPIC GUIDANCE AND NAVIGATION TECHNIQUES - Bilhar,Romero Pinto de Oliveira (2018)
ABSTRACT Objectives: To compare the accuracy of insertion of pedicle screws into the thoracic spine using fluoroscopic guidance or computer-assisted navigation techniques. Methods: Eight cadaveric thoracic spines were divided into two groups: the fluoroscopy group, in which pedicle screws were inserted with the guidance of a C-arm device, and the navigation group, in which insertion of the screws was monitored using computer-assisted navigation equipment. All procedures were performed by the same spinal surgeon. The rate of pedicle breach was compared between the two groups. Results: There was one intra-canal perforation in each group. Both perforations were medial in direction, and the breaches were 2 to 4 mm deep. There were no statistically significant differences in breach rate between the two groups. Conclusions: The accuracy of insertion of pedicle screws in the thoracic spine using computer-assisted navigation is equivalent to that achieved using fluoroscopic guidance. Computer-assisted navigation improves the safety of the surgical team during the procedure due to the absence of exposure to radiation. Therefore, there is a need for future randomized controlled trials to be conducted in the clinical setting to evaluate other outcomes, including duration of surgery and blood loss during the procedure. Level of evidence IV.